An Overview of Candida-associated Gastric Ulcer Until Yesterday, Today, and from Tomorrow — In Quest of the Etiology — - Kenji Sasaki (Challenges in Disease and Health Research Vol. 5, 2021)
Candida-associated gastric ulcer, though formerly thought to affect only debilitated persons, has been reported to occur in apparently healthy individuals. Though had been reported to demonstrate nothing but nonspecific endoscopic features, the disease occasionally exhibits an apparently typical finding the author designated a candidarium. The natural history of the disease had been unknown but the ulcer is shown not only to occur but also to recur in a different site with a different shape in a non-diabetic, Helicobacter pylori (H. pylori)-negative, apparently immunocompetent patient without antecedent ulcers or history of the lesions, who has not been given non-steroidal anti-inflammatory drugs (NSAIDs), antibiotics, antineoplastic agents, systemic corticosteroids which implies that Candida is no innocuous bystander but an etiologic perpetrator. Immune deficiency has recently been reported in relation to candidiasis, which might explain the cause of intractable Candida-associated gastric ulcer. In the oropharyngeal field, Candida albicans has recently been shown to secrete a hitherto unknown cytolytic peptide pore-forming toxin (PFT), candidalysin, into a pocket in the epithelium which it penetrates into and to activate mitogen-activated protein kinase (MAPK)/MAPK phosphatase 1 (MKP1)/c-Fos pathway, triggering release of damage as well as immune cytokines. While the PFT, exerting an effect even on the adjacent cells, directly injures the tissue with damage cytokines, it induces immune counterparts to activate polymorphonuclear leukocytes (PMN) to eventually terminate inflammation, which results in restoring the fungus to the commensal state or eradicating it. Since it cannot be negated that such a phenomenon occurs in the gastric mucosa, a theoretically strong possibility has come up that the so-called Candida-associated gastric ulcer is actually Candida-induced ulcer. Owing to the recent advances in microbiology, molecular biology, and immunology, a logically definitive possibility has emerged that the so-called Candida-associated gastric ulcer is Candida-induced ulcer. The disease has come to a stage, in which the etiology should be reinvestigated and the disease itself should be reconsidered in the light of not only pathogens’ character but also hosts’ immunological status Therefore, the disease should be reinvestigated in the light of the recent immunological, microbiological, and molecular biological findings.